FORECASTING THE RISK OF CARDIOVASCULAR COMPLICATIONS BASED ON CLUSTER ANALYSIS OF QT INTERVAL IN CHILDREN WITH TYPE 1 DIABETES (World Science, 2021)
Clinical and scientific experience of curation and analysis of children with type 1 diabetes and with acquired or congenital long QT syndrome (LQTS) health is not enough discovered for full control, treatment and risks prediction. Іn this work we investigated interconnection of type 1 diabetes in children and possibility of cardiovascular disorders taking into account the results of twenty-four-hour Holter ECG monitoring and measurement of QT and QTc in 3 leads (CM5, CS1, CS3) . To predict the risk of cardiovascular complications in the form of sudden ventricular life-threatening tachyarrhythmias, we made an assessment of risk groups using hierarchical cluster analysis and determined three groups. The low-risk group included children who did not have an increase in the duration of QT and QTc intervals in any of the leads; the high-risk group included children who had an increase in the duration of the QT and QTc intervals and the variance of these intervals in several leads simultaneously. The medium-risk group included children who had prolongation of QT and QTc intervals in only 1 lead or had a change in the variance of these intervals. According to the results of our analysis, the main goal of reducing the risk of life-threatening complications in children with type 1 diabetes is the timely diagnosis of long QT interval syndrome, especially its congenital form, for further management of these patients at simultaneous appointment of insulin therapy and correction of episodes of hypoglycemia, which can impair a course of a syndrome of the prolonged QT interval.